2013
DOI: 10.1186/1742-4755-10-41
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of Ottawa university students’ awareness, knowledge and perceptions of infertility, infertility risk factors and assisted reproductive technologies (ART)

Abstract: BackgroundAwareness of infertility risk factors is an essential first step to safeguard future fertility. Whereas several studies have examined university students’ awareness of female fertility and related risk factors, the topic of male infertility has not been well examined. The objective of this study was to assess young men and women’s awareness, knowledge and perceptions of infertility, male and female infertility risk factors and assisted reproductive technologies (ART).MethodsSemi-structured interviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 58 publications
4
57
0
5
Order By: Relevance
“…This observation is in accordance with the BInternational Fertility Decision-making Study^and other studies that observed a modest level of fertility knowledge of participants and that participants overestimated the age at which a women's ability to become pregnant first declines, the chance to become pregnant under optimal conditions and the chance of conception after IVF [12,18,19,25,27,33,34]. Our study might have overstated knowledge gaps for some questions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This observation is in accordance with the BInternational Fertility Decision-making Study^and other studies that observed a modest level of fertility knowledge of participants and that participants overestimated the age at which a women's ability to become pregnant first declines, the chance to become pregnant under optimal conditions and the chance of conception after IVF [12,18,19,25,27,33,34]. Our study might have overstated knowledge gaps for some questions.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies reported knowledge gaps concerning fertility awareness, parenting attitudes, and specific factors influencing fertility in students in Europe [10][11][12][13][14][15][16][17], Asia [18][19][20], Africa [21], Australia [22,23], Canada [24,25], and the USA [26,27]. These studies have investigated the knowledge of young people or students, but little is known about the attitude of students towards ART and oocyte freezing as well as the differences in knowledge about fertility in special groups, e.g., medical and non-medical students and between sexes.…”
Section: Introductionmentioning
confidence: 99%
“…It is being thought that severe military conflicts in Africa shorten the expected lifetime for more than 2 years. In general, WHO had calculated that 269 thousand people had died in 1999 due to the effect of wars and that loss of 8.44 million healthy years of life had occurred (2,3). Wars negatively affect the provision of health services.…”
Section: War and Women's Healthmentioning
confidence: 99%
“…The estimated fertility rate in Canada is 11.5% to 15.7%. One out of seven English couples suffers from fertility problems (3). The number of couples affected by infertility has increased from 42.0 million people (39.6 million people, 44.8 million people) in 1990 to 48.5 million people (45.0 million people, 52.6 million people) in 2010 (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation